KEBIJAKAN HUKUM PIDANA TERHADAP PELECEHAN SEKSUAL BERBASIS GENDER DI MEDIA SOSIAL - Desmawita Desmawita; Mukhlis R; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
Referring to Komnas Perempuan's 2020 Annual Notes, it notes that thereis a new type of gender violence, namely cyber-based or online gender violence.Cases of violence have continued to increase over the last six years, an increaseof 300% in Online Gender Based Violence (KBGO) compared to the previousyear (2019). Komnas Perempuan stated that this type of violence has anincreasingly complicated pattern of violence because it occurs in the digitalrealm. Ranging from character assassination to sexual harassment through cyberattacks.The type of research used is normative juridical research. In this research,the researcher discusses the level of legal synchronization, which aims to revealthe extent to which certain laws are compatible vertically or horizontally with thismatter.The conclusions that can be drawn from the results of the study are: First,the current criminal law regulation against gender-based sexual harassment onsocial media has not fully supported the advancement of internet technology. Thistype of violence is the same as direct violence, the difference is that now gender-based violence has shifted to social media or cyberspace. Therefore, social mediais considered not to have a safe space for women. To get protection for KBGO onsocial media. Second, the ideal idea of gender-based sexual harassment on socialmedia in the future is that the PKS Law actually has articles that regulate humanrights. These articles can also be used as a reference to fulfill women's sense ofsecurity and rights to freely surf the internet or social media. These articlesinclude Article 27 Paragraph 1 and Article 45 Paragraph 1 concerning theElectronic Information and Technology (ITE) Law which is still being debatedbecause it is considered a rubber article, Article 28E Paragraph (3) of the 1945Constitution and Article 19 Universal Declaration of Human Rights on freedom ofexpression, Article 28G Paragraphs (1) and (2) of the 1945 Constitution andArticle 17 Paragraph (1) of the International Covenant on Civil and PoliticalRights concerning the right to security and privacy, and Article 29 of thePornography Law.Keywords: Criminal Law Policy, Sexual Harassment, Gender, Social Media.